PEMETAAN BEBERAPA CIRI KIMIA TANAH DI NAGARI SITIUNG KECAMATAN SITIUNG KABUPATEN DHARMASRAYA - Gunadi Gunadi; Juniarti Juniarti; Gusnidar Gusnidar (Jurnal Solum, 2017)
Sitiung located in Dharmasraya, West Sumatera has 5804.3 haarea which was dominated by smallholder agriculture. The soil chemical properties in Sitiung village were often analysed by some scientists, but there was no map yet provided for the soil properties information. The purpose of the study was to determineand tocreate mapofsomesoil chemical characteristics in Sitiung Village, Sitiung District, Dharmasraya Regency. The study was conducted using a survey method, as well as spatial data analysis model. Soil sampling were taken in purposive random sampling under several land units (LU), the land units (LU) were limited by soil order, slopes, and land use. LU 1: Ultisols, flat, mixed garden; LU 2: Ultisols, flat, rice; LU 3: Entisols, flat, rice; LU 4: Entisols, flat, mixed garden; LU 5: Entisols, mild, shrubs; LU 6: Oxisols, mild, shrubs; LU 7: Entisols, mild, oil palm; LU 8: Entisols, flat, oil palm; LU 9: Oxisols, mild, oil palm; LU 10: Oxisols, flat, oil palm; LU 11: Ultisols, mild, oil palm; LU 12: Oxisols, steep, oil palm. Parameters analysed were pH, Al-exchangable, organic-C, total-N, P-available, CEC, and base saturation. The spatial data analysis and data processing were used to transform soil analysis results into a thematic soil map.The result showed that the highest pH value was 5.76 (slightly acid) found in LU 3, and the lowest pH value was 4.37 (highly acid) in LU 10. The highest Al-exchangable was 9.72 cmol/kg in LU 6, while the lowest value was 0.92 cmol/kg in LU3. Furthermore, the highest value oforganic-C was 3.12 % (high) in LU 2, and the lowest was 1.78 % (low) in the LU 6. The total-N content wasmedium. The highest content of P-available was 14.7 ppmin LU 10, and the lowest was 7.93 ppm (low) in the LU 4. The highest CEC was 12.74 cmol/kg (low) and the lowest was 4.70 cmol/kg (very low) in LU 7. The basic cation content was found to be low to moderate.Keyword: Land Unit, Sitiung Village, Soil chemical properties, Thematic soil map